CONCEPTUAL FRAMEWORKS FOR PLANNING OF THE DEVELOPMENT OF HIGHER EDUCATION INSTITUTIONS - Polyanska, A. S.; Tymoshenko, D. V. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The article substantiates the feasibility of developing a strategy of higher educational institution. The conducted researches allows us to assert that strategic planning of higher educational institutions development (concerning the context of strategy development) is justified by modern trends in country's economy development, requirements of globalization, innovative development, integration of Ukraine into the European and world space. The strategy of higher educational institution is a strategic plan for its development, which determines the priorities of institutional activities and ways to achieve them. It is noted that the classical approach to strategic planning contains a wide range of planning tools and methods, although it is not often used in management practice of educational institutions. Given the complexity of functioning environment of higher educational institution, the difficult period of reform of higher education, as well as threats and weaknesses in its activities, attention is focused on development of conceptual frameworks, that is key requirements for the creation of strategic document with the ways of its implementation both at the level of entire organization and its structural units. Algorithmics of forming the strategy of higher educational institution is submitted, which begins with the assessment of functioning environment; thus, the international experience is taken into account. Attention is drawn to the use of modern planning techniques during strategic planning, which allows consideration of the features and priorities of not only the institution of higher education, but also its structural units, on the performance results of which the success and competitiveness of the institution depend. The emphasis is put on defining key indicators of institution development, which should not only meet the standards and requirements of higher education, but also assess the potential opportunities for the formation of added value by creating competitive advantages and emphasizing uniqueness. Special attention is paid to the strategic planning process of proper organization. In practice, this work is carried out by a specially formed Committee and Working Groups, taking into account the fact that the development of strategy of higher educational institution should involve specialists who will carry out agreed and approved strategic goals and operational objectives. It is also recommended to take into account possible managerial shortcomings and errors in planning, which are described in this paper.